An investigation into biochar, acid-modified biochar, and wood vinegar on the remediation of saline−alkali soil and the growth of strawberries - Pan, Xin; Shi, Mei; Chen, Xichao; Kuang, Shaoping; Ullah, Habib; Lu, Hongxiu; Riaz, Luqman (Frontiers in Environmental Science, 2022)
Global food security and biodiversity are seriously threatened by the salinization of several hundred million hectares of land. Biochar and wood vinegar amendment has been suggested as a possible way to promote plant productivity and improve soil qualities. Whereas, Less emphasis has been paid for the application of biochar in saline-alkaline soils to increase plant productivity. Herein, we introduced sawdust wood vinegar, sawdust biochar and its acid-modified biochar and alone or in combination for soil amendments and provided first insight to study their effect on the restoration of coastal saline-alkali soil and plant growth of strawberry seeding. Proximate, ultimate analysis and different characterization techniques such as FTIR and SEM were applied to study the physicochemical characteristics of raw and modified biochar. Our results revealed that acid-modified biochar show the most significant promote effect on the strawberry growth,which could increase the weight gain rate, root length, root specific surface area and root volume of strawberry seedlings by 41.2%, 18.9%, 23.0% and 34.7% , respectively. Moreover, the application of acid-modified biochar can effectively alleviate soil salinization by reducing soil pH (7.65) and CEC (19.5cmol/kg). Furthermore, the addition of biochar can significantly improve the community structure of microorganisms (Proteobacteria) and increase the content of bacteria related to soil nutrient cycling (Pseudomonadaceae and Sphingomonadaceae). Preliminary findings from this study suggest that acid-modified biochar is a potentially effective means of preventing soil salinization and increased economic crop yields.